Further studies of neuroangiostrongyliasis (rat lungworm disease) in Australian dogs: 92 new cases (2010–2020) and results for a novel, highly sensitive qPCR assay. Issue 2 (24th February 2021) - Lee, Rogan; Pai, Tsung-Yu; Churcher, Richard; Davies, Sarah; Braddock, Jody; Linton, Michael; Yu, Jane; Bell, Erin; Wimpole, Justin; Dengate, Anna; Collins, David; Brown, Narelle; et al.
Abstract: The principal aim of this study was to optimize the diagnosis of canine neuroangiostrongyliasis (NA). In total, 92 cases were seen between 2010 and 2020. Dogs were aged from 7 weeks to 14 years (median 5 months), with 73/90 (81%) less than 6 months and 1.7 times as many males as females. The disease became more common over the study period. Most cases (86%) were seen between March and July. Cerebrospinal fluid (CSF) was obtained from the cisterna magna in 77 dogs, the lumbar cistern in f5, and both sites in 3. Nucleated cell counts for 84 specimens ranged from 1 to 146 150 cells μ L −1 (median 4500). Percentage eosinophils varied from 0 to 98% (median 83%). When both cisternal and lumbar CSF were collected, inflammation was more severe caudally. Seventy-three CSF specimens were subjected to enzyme-linked immunosorbent assay (ELISA) testing for antibodies against A. cantonensis ; 61 (84%) tested positive, titres ranging from <100 to ⩾12 800 (median 1600). Sixty-one CSF specimens were subjected to real-time quantitative polymerase chain reaction (qPCR) testing using a new protocol targeting a bioinformatically-informed repetitive genetic target; 53/61 samples (87%) tested positive, C T values ranging from 23.4 to 39.5 (median 30.0). For 57 dogs, it was possible to compare CSF ELISA serology and qPCR. ELISA and qPCR were both positive in 40 dogs, in 5 dogs the ELISA was positive while the qPCR was negative, in 9 dogs the qPCR was positive but the ELISA was negative, while in 3 dogs both the ELISA and qPCR were negative. NA is an emerging infectious disease of dogs in Sydney, Australia.